2018
DOI: 10.1515/snde-2016-0019
|View full text |Cite
|
Sign up to set email alerts
|

A multivariate regime-switching GARCH model with an application to global stock market and real estate equity returns

Abstract: Abstract:We consider a multivariate Markov-switching GARCH model which allows for regime-specific volatility dynamics, leverage effects, and correlation structures. Conditions for stationarity and expressions for the moments of the process are derived. A Lagrange Multiplier test against misspecification of the within-regime correlation dynamics is proposed, and a simple recursion for multi-step-ahead conditional covariance matrices is deduced. We use this methodology to model the dynamics of the joint distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 79 publications
0
15
0
Order By: Relevance
“…Nomikos, Alizadeh and Pouliasis [27] showed that RS BEKK was suitable for futures markets (based on USA data). A significant contribution was provided by Haas and Mittnik [19]. They thoroughly defined a multivariate generalization of the RS GARCH model (diagonal VEC model).…”
Section: Previous Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Nomikos, Alizadeh and Pouliasis [27] showed that RS BEKK was suitable for futures markets (based on USA data). A significant contribution was provided by Haas and Mittnik [19]. They thoroughly defined a multivariate generalization of the RS GARCH model (diagonal VEC model).…”
Section: Previous Researchmentioning
confidence: 99%
“…In the following year, Chen [12] focused on the CCC model. He elaborated that in the model in [19], it was difficult to estimate the correlations. The reason for this is that when a correlation changes, the degree of change in the variance of one return or the other affecting the correlation is unknown.…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, our contribution is to examine the interactions between Gold and alternative classes of assets, not only in a time-varying fashion using a bivariate GARCH (with return and volatility spillovers), but also enabling these interactions to evolve depending on the regime under consideration. More precisely, this paper implements a BEKK model with Markov-switching -the MS-BEKK by Haas and Mittnik (2008) -on Gold, S&P 500, Bonds, Crude Oil, Silver, Platinum and Palladium, from 1988to 2013 In this modeling framework, Haas, Mittnik, and Paolella (2004), Kasch and Caporin (2013) provide recent applications to, respectively, exchange rate and equity dynamics in order to study cross-market dependencies conditional on volatility regimes.…”
Section: Introductionmentioning
confidence: 99%
“…stocks, bonds, crude oil) on the other hand. The econometric methodology relies on the Markov-switching BEKK model by Haas and Mittnik (2008) that captures time-varying correlations and bull-bear regimes for bivariate specifications. The model is applied to daily data from 1988 to 2013.…”
mentioning
confidence: 99%